Adaptability of Napiergrass (Pennisetum purpureum Schumach.) for Weed Control in Site of Animals Buried after Foot-and-Mouth Disease Infection. (4th May 2016) - Ishii, Yasuyuki; Iki, Yusuke; Inoue, Kouhei; Nagata, Shuhei; Idota, Sachiko; Yokota, Masato; Nishiwaki, Aya
Abstract : After the infection of foot-and-mouth disease outbreaks in Miyazaki, Japan, in 2010, cattle and swine were slaughtered and buried in a site of 100 ha, where weed control is difficult and costly since lands are unlevelled and prohibited to be plowed for 3 years. To consider the adaptability of napiergrass ( Pennisetum purpureum Schumach.) to the animal burial site for weed control, two napiergrass varieties, normal Wruk wona (WK) and dwarf late-heading variety (DL), were transplanted, compared with sowing of maize (MZ) and sorghum (SR) in both burial (BU) and neighboring bordered area (BO) in mid-June 2011. Even though several weed control methods were subjected to lands, MZ and SR failed to be established stably at only 1/3–1/2 due to the suppression of growth by indigenous weeds, while WK and DL successfully established as high as 82–91% and 73–85%, respectively, in 2011. The poor establishment of MZ and SR after sowing tended to be increased with the year from establishment. Plant dry matter yield and cellulose concentration were the highest in WK in 2011, while overwintering ability was constantly higher in DL in the 3 years. It is necessary to consider the utilization of forage plants on the animal burial site.